Synthesis and morphology evolution of lead-free piezoelectric K 1/2Na1/2NbO3 powder at low temperature - Nopsiri Chaiyo (2018)
A synthetic route for modified solid state reaction has been developed for the synthesis of the perovskite phase of potassium sodium niobate, K1/2Na1/2NbO3 (KNN). Potassium oxalate monohydrate (K2C2O4.H2O) and sodium oxalate (Na2C2O4) were employed as a source of potassium and sodium, respectively. The formation of the K1/2Na1/2NbO3 phase was investigated as a function of calcination conditions by TG-DTA and XRD techniques. Morphology and particle size were determined via an SEM technique. It was found that the minor phases of Na2CO3 and K2CO3 tend to form together with K1/2Na1/2NbO3, depending on calcination conditions. The perovskite phase was successfully synthesized at a low temperature of 400°C. As calcination temperatures increased from 600° to 850°C, the KNN solid solution became more homogeneous, XRD peaks became narrower, and a pattern similar to that expected for orthorhombic K1/2Na1/2NbO3 was achieved after 600°C, as indicated by the separate peaks of 0 2 2 and 2 0 0. Copyright © Taylor & Francis Group, LLC.